Psychological Interventions for Individuals With Acquired Brain Injury, Cerebral Palsy, and Spina Bifida: A Scoping Review - Jefferies, Morgan; Peart, Taylor; Perrier, Laure; Lauzon, Andrea; Munce, Sarah (Frontiers in Pediatrics, 2022)
Background: With current medical advancements, more adolescents with neurodevelopmental disorders are transitioning from child- to adult-centred health care services. Therefore, there is an increasing demand for transitional services to help navigate this transition. Health care transitions can be further complicated by mental health challenges prevalent among individuals with cerebral palsy (CP), spina bifida (SB), and childhood onset acquired brain injury (ABI). Offering evidence-based psychological interventions for these populations may improve overall outcomes during transition period(s) and beyond. The objective of this scoping review is to identify key characteristics of psychological interventions being used to treat the mental health challenges of adolescents and adults with CP, SB, and childhood onset ABI. Methods: Methodological frameworks by Arksey and O’Malley, and Levac and colleagues were used to explore studies published between 2009 and 2019. Included studies were required to be written in English and report on a psychological intervention(s) administered to individuals 12+ years of age with a diagnosis of CP, SB, or childhood onset ABI. All study designs were included. Results: A total of 11 studies were identified. Of these, eight reported psychological interventions for childhood onset ABI, while three reported on CP. No studies reporting on SB were identified. Commonly used interventions included acceptance and commitment therapy (ACT), psychotherapy, and cognitive behavioural therapy (CBT). Conclusions: There are a limited number of studies investigating psychological interventions for individuals with childhood onset ABI and CP, and none for individuals with SB. Further research into effective psychological interventions for these populations will improve mental health outcomes and transitional services.